The genus Arrhopalites Börner, 1906 (Collembola, Appendiciphora, Arrhopalitidae) in the Neotropical Region, with description of four new cave species from Brazil - Zeppelini, Douglas (Zootaxa, 2006)
Twenty two known and new Neotropical species of the genus Arrhopalites (Collembola: Arrhopalitidae) are revised and diagnosed. The four new cave species from Brazil are described and illustrated and the remaining Brazilian and Mexican species are redescribed and illustrated. Neotropical species are distributed along the Good’s biogeographic zones 8, 24a, 27 and 29. Four species described as Arrhopalites are replaced in the genus Pararrhopalites Bonet & Tellez 1944 based on their morphology. A short discussion is made about the distribution of the genus in the Neotropical Region, and a key for identification of the Neotropical species is provided.